Towards a hybrid compactification with a scalar-tensor global cosmic string - Abdalla, M. C. B. [UNESP]; Guimaraes, M. E. X.; da Silva, J. M. Hoff [UNESP] (Iop Publishing Ltd, 2008)
We derive a solution of the gravitational equations which leads to a braneworld scenario in six dimensions, using a global cosmic string solution in a low energy effective string theory framework. The final spacetime is composed by one warped brane with R((3,1)) x S(1) topology and a power law warp factor, and one non-compact extra dimension transverse to the brane; by looking at the current experimental bounds, we find a range of parameters in which, if the on-brane dimension has an acceptable size, it does not solve the hierarchy problem. In another example, this problem is smoothed by means of the Brans-Dicke parameter.
Keywords: string theory and cosmology; cosmological applications of theories with extra dimensions; cosmic strings; domain walls; monopoles